Hydrazine‐assisted liquid exfoliation of MoS2 for catalytic hydrodeoxygenation of 4‐methylphenol - Liu, G; Ma, H; Teixeira, I; Sun, Z; Xia, Q; Hong, X; Tsang, S (Wiley, 2016)
A simple but effective method to exfoliate bulk MoS2 in a range of solvents is presented for the preparation of colloid flakes consisted of one to a few molecular layers by application of ultrasonic treatment in N2H4. Their high yield in solution and exposure of more active surface sites allows the synthesis of corresponding solid catalysts with remarkably high activity in hydrodeoxygenation of 4‐methylphenol and this method can also be applied to other two dimensional materials.